Women’s Morals in the Qur’an: Study of Nadirsyah Hosen’s Thoughts in ”Tafsir Qur’an di Medsos: Mengkaji Makna dan Rahasia Ayat Suci pada Era Media Sosial” - Najiburrohaman, Najiburrohman; Habsyi, Nabila (TAJDID, 2023)
Issues regarding women are still widely discussed by the general public, so there are several individuals who take advantage of these issues to gain personal gain. Women who are victims of sexual harassment have been judged badly by society because their disgrace has spread widely and has always become a hot trending topic in magazines, newspapers, television and social media. Therefore, researchers really want to examine the thoughts of an Indonesian academic, namely Nadirsyah Hosen, regarding women's morals as stated in the QS. An-Nur: 31 in ”Tafsir Al-Quran di Medsos: Mengkaji Makna dan Rahasia Ayat Suci pada Era Media Sosial”. This article uses qualitative methods with descriptive analysis, literature review and a thematic approach. The primary data in this article comes from the Al-Qur'an and the book “Tafsir Al-Quran di Medsos: Mengkaji Makna dan Rahasia Ayat Suci pada Era Media Sosial”, for secondary data using several books and journals that are appropriate to the discussion. This article explains how women’s morals are in this modern era, with the aim that women, especially teenagers, can return (again) to the correct religious sharia. Researchers concluded that it is mandatory for women to wear a large khimar (cover) that covers their chest and forbids women from offering tabarruj to men who are not their mahram.